Idiosyncratic drug‐induced liver injury: A short review. Issue 6 (28th June 2017) - Yamashita, Yo‐ichi; Imai, Katsunori; Mima, Kosuke; Nakagawa, Shigeki; Hashimoto, Daisuke; Chikamoto, Akira; Baba, Hideo
Abstract : Idiosyncratic drug‐induced liver injury (iDILI) is a rare adverse drug reaction that occasionally leads to acute liver failure or even death. An aging population that uses more drugs, a constant influx of newly developed drugs, and a growing risk from herbal and dietary supplements of uncertain quality can lead to an increase in iDILI. Antimicrobials, central nervous system agents, and herbal and dietary supplements are the most common causes of iDILI in developed countries. iDILI is still a diagnosis of exclusion, and thus careful history taking and thorough work‐ups for competing etiologies, such as acute viral hepatitis, autoimmune hepatitis, and others, are essential. The pathogenesis of iDILI is not clear and includes a mix of host reactions, drug metabolites, and environmental factors. Immediate cessation of the suspected offending drug is key to preventing or minimizing progressive damage. No definitive therapies for iDILI are available, and the treatments remain largely supportive. ( Hepatology Communications 2017;1:494–500)